Effect of Long-Term Moderate Physical Exercise on Irisin between Normal Weight and Obese Men - Farah A. Rashid; Hamid Jaddoa Abbas; Naser Ali Naser; Hana'a Addai Ali (The Scientific World Journal)
Background. Irisin is a myokine that has a beneficial effect on obesity and glucose metabolism by increasing energy expenditure. This study aims to investigate the effect of long-term moderate physical exercise on irisin levels and its correlations with body mass index (BMI), waist circumferences (WC), and metabolic parameters in normal weight and obese males. Material and method. A follow-up case-control study of sixty male participants, comprised of thirty normal weight and thirty obese, who had undergone supervised long-term moderate physical exercises for six months. Serum irisin levels, fasting blood glucose, serum insulin, homeostatic model assessment of the insulin resistance index (HOMA-IR), and β-cell function (HOMA-B2) were assessed. Results. Long-term moderate exercise induced elevation of the irisin level significantly (P<0.0001) with significant reduction of the BMI, WC, fasting blood glucose, insulin, HOMA-IR, and HOMA-B2 levels (P<0.0001) in comparison between obese and normal weight groups. There are significant differences for each parameter in each obese and normal weight group before and after physical exercise with exception of the BMI and WC in the normal group. Significant negative correlations were shown between irisin and blood glucose and insulin and HOMA-IR levels in the obese group and normal weight group. Conclusion. Irisin improves glucose homeostasis after long-term moderate physical exercises, suggesting that irisin could have regulatory effect on glucose, insulin resistance, and obesity and it could be used as a potential therapy for obesity and insulin resistance.